The Effect of Spiritual Leadership, Servant Leadership, and Organizational Culture on Employee Engagement among Millennial Employees at Hospital X in Cirebon - Sugiarti, Ade Rizki; Afiyah, Nada Nur; Febrianti, Sofi; Alifa, Wina Dzihni (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Employee engagement is an important factor in improving employee performance and service quality, particularly among millennial employees who dominate the workforce in the healthcare sector. A high level of employee engagement is essential for hospitals as service-oriented organizations to ensure optimal patient care. This study aims to examine the effects of spiritual leadership, servant leadership, and organizational culture on employee engagement among millennial employees at Hospital X in Cirebon. Data were collected through a survey using structured questionnaires distributed to 70 (seventy) employees of Hospital X in Cirebon using a non-probability sampling technique. Data analysis was conducted using multiple linear regression, accompanied by validity and reliability tests. The results indicate that spiritual leadership has a positive and significant effect on employee engagement, servant leadership does not have a significant effect, and organizational culture has a positive and significant effect on employee engagement among employees at Hospital X in Cirebon.